(untitled) (Baltic Journal of Sport and Health Sciences, 2019)
Background. The behaviour of physical education (PE) teachers in managing the lesson is significantly related to their life satisfaction (Bahadir, 2013). PE teachers’ self-report of emotional abilities is positively associated with the educational achievements of their students and increasing teachers’ self-report of emotional abilities improves the quality of physical education (Buns & Thomas, 2016). High self-report of emotional abilities reduces the impact of work-related stress on teachers, increases their creativity in classroom activities and increases students’ satisfaction with physical activities (Huang, Liu, Hsieh, & Chang, 2015). The aim of this study was to evaluate physical education teachers’ self-report of emotional abilities and subjective quality of life in comparison with teachers of other subjects, so that in the future more effective measures for improving teachers’ self-report of emotional abilities and subjective quality of life could be developed. Methods. To collect data, Schutte SSRI and SF-36 questionnaire survey was applied. Results. We found that, according to some sub-scales, men and women were significantly (p < .05) different in the estimation of their subjective quality of life. Women scored better (higher scores) than men in their physical performance, emotional state, energy/fatigue, and perceived pain. In this study, we revealed significant correlations between social skills and appraisal (r = .305, p < .01), emotional well-being and appraisal (r = .214; p < .05), and energy/fatigue and appraisal (r = .209; p < .05). The data obtained in our study revealed that male and female teachers evaluated their ability to understand and analyze emotions and manage emotions differently (p < .05). Conclusions. Teachers’ self-report of emotional abilities differed significantly by appraisal and utilization and by the subject taught, which differed in optimism, appraisal, and utilization. Significant (p < .05) differences in subjective quality of life were found by gender in to physical functioning, emotional well-being, energy/fatigue, and pain. There was no significant difference found in subjective quality of life by the subject taught. Keywords: physical education, teacher, self-report of emotional abilities, subjective quality of life.